2016
DOI: 10.1152/ajprenal.00049.2016
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced kidney hypoxia precedes albuminuria in type 1 diabetic mice

Abstract: Intrarenal tissue hypoxia has been proposed as a unifying mechanism for the development of chronic kidney disease, including diabetic nephropathy. However, hypoxia has to be present before the onset of kidney disease to be the causal mechanism. To establish whether hypoxia precedes the onset of diabetic nephropathy, we implemented a minimally invasive electron paramagnetic resonance oximetry technique using implanted oxygen sensing probes for repetitive measurements of in vivo kidney tissue oxygen tensions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…37 It was reported that increasing kidney QO 2 using the chemical mitochondrial uncoupler 2,4-dinitrophenol to increase mitochondrial leak respiration resulted in kidney hypoxia and development of nephropathy, independently of oxidative stress or hyperglycaemia. 28 Recently, it was shown that kidney hypoxia precedes the development of proteinuria in insulinopenic diabetes 38 and that pharmacological activation of the hypoxia-inducible factor (HIF) system prevented diabetesinduced mitochondrial uncoupling, kidney hypoxia and proteinuria. 39 The chronic hypoxia theory is also supported by studies in humans.…”
Section: Discussionmentioning
confidence: 99%
“…37 It was reported that increasing kidney QO 2 using the chemical mitochondrial uncoupler 2,4-dinitrophenol to increase mitochondrial leak respiration resulted in kidney hypoxia and development of nephropathy, independently of oxidative stress or hyperglycaemia. 28 Recently, it was shown that kidney hypoxia precedes the development of proteinuria in insulinopenic diabetes 38 and that pharmacological activation of the hypoxia-inducible factor (HIF) system prevented diabetesinduced mitochondrial uncoupling, kidney hypoxia and proteinuria. 39 The chronic hypoxia theory is also supported by studies in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This could be relevant in the pathogenesis of diseases that are associated with low oxygenation at night, such as obstructive sleep apnea and the associated progression of renal disease. One could argue that diseases associating with kidney hypoxia, for instance CKD (Evans et al, 2013) and diabetes (Franzen et al, 2016), could be more progressive during the resting phase. On the other hand, our data may also provide a new look at the association of neglecting to align with the inner circadian clock (e.g., in shift workers) with the development of hypertension and CKD (Lieu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, alteration in renal oxygen consumption and tissue hypoxia has been demonstrated in both diabetic and non-diabetic CKD models prior to the development of structural changes (Ries et al, 2003; Manotham et al, 2004; dos Santos et al, 2007; Deng et al, 2009, 2010; Franzén et al, 2016). Moreover, kidney hypoxia resulting from increased mitochondrial oxygen consumption alone has been shown to induce kidney injury (Friederich-Persson et al, 2013).…”
Section: Pathophysiology Of Hypoxia In Ckdmentioning
confidence: 99%
“…They concluded that kidney tissue hypoxia, per se , may be sufficient to initiate the development of nephropathy. Others have demonstrated the presence of tissue hypoxia in the kidney before the onset of albuminuria in diabetic mice (Franzén et al, 2016). Functional MRI imaging techniques have also been used to assess intrarenal oxygenation in humans, specifically in diabetic patients.…”
Section: Renal Oxygenation In Diabetic Ckdmentioning
confidence: 99%